Enhancing the Capture Capabilities of LoRa Receivers - Edward, Phoebe; Muhammad, Abdullah; Elzeiny, Sondos; Ashour, Mohamed; Elshabrawy, Tallal; Robert, Joerg (2019 International Conference on Smart Applications, Communications and Networking, SmartNets 2019, 2019)
In recent years, LoRa has quickly established its footprint to become a leading Low Power Wide Area Network (LPWAN) technology. LoRa is envisaged to accommodate a diverse set of dense smart city use cases. Accordingly, in light of the simple ALOHA medium access adopted by LoRa, collision between different LoRa signals is inevitable. Nevertheless, the patented LoRa modulation has inherent potential for strong capture capabilities to survive some co-Technology interference. Our experiments using the Dragino LoRa Shield which is based on the SX1276 LoRa transceiver have shown that it captures a received packet when it detects 4 consecutive identical preamble upchirp signals as previously found in the literature. In this paper, we investigate different preamble detection schemes, by which we refrain from the consecutive constraint. In this regard, we develop an SDR-based testbed that generates LoRa-like signals with different/controlled co-Technology collision scenarios. Experimental results show that relieving the consecutive constraint could significantly improve the LoRa capture capability. Detecting the preamble using 3 non-consecutive similar symbols instead of 4 consecutive has increased the percentage of captured packets by 11.12% for SIR 6 dB. Moreover, using the downchirp signals within the preamble, the captured packets can be further synchronized. Results show that the percentage of correctly synchronized packets has increased by 10.29 % for SIR 6 dB using the 3 non-consecutive preamble detection scheme instead of the 4 consecutive scheme.
CRIS-Team Scopus Importer:2024-11-19
Keywords: Capture Effect; LoRa Modulation; LP-WAN; Preamble Detection; SDR